Free DNA and Metagenomics Analyses: Evaluation of Free DNA Inactivation Protocols for Shotgun Metagenomics Analysis of Human Biological Matrices - Mancabelli, Leonardo; Milani, Christian; Anzalone, Rosaria; Alessandri, Giulia; Lugli, Gabriele Andrea; Tarracchini, Chiara; Fontana, Federico; Turroni, Francesca; Ventura, Marco (Frontiers in Microbiology, 2021)
Culture-independent approaches now represent the gold standard for the investigation of both environmental and host-associated complex microbial communities. Nevertheless, despite the great advantages offered by these novel methodologies based on the use of next-generation DNA sequencing approaches, a number of bias sources have been identified. Among the latter, free DNA contained in biological matrices is one of the main sources of inaccuracy in reconstructing the resident microbial population of viable cells. For this reason, the photoreactive DNA-binding dye Propidium MonoAzide (PMAxx™) has been developed by improving standard propidium monoazide (PMA). This compound binds and inactivates free DNA, thus preventing its amplification and sequencing. While the performances of PMA have been previously investigated, the efficiency with PMAxx™ has been tested mainly for amplicon-based profiling approaches on a limited number of biological matrices. In this study, we validated the performance of PMAxx™ for shotgun metagenomics approaches employing various human-associated matrices. Notably, results revealed that the effectiveness of PMAxx™ in inactivating free DNA of prokaryotes and eukaryotes tend to vary significantly based on the biological matrices analyzed.